Padre Harry Martin Brown (1889–1983) and the British West Indies Regiment (BWIR), ‘Under Empire,’ During the First World War - Allison, Neil E. (Baptist quarterly, 2021)
The First World War was a catalyst for the beginning of incredible social change within British Society and within its Empire. Part of that Empire included the British West Indies and the British West Indies Regiment (BWIR) was formed to promote British War aims during the First World War. West Indies soldiers were not well respected by the British authorities simply because of their race and they suffered much neglect in the cold and wet of France. Padre Harry Martin Brown, a Baptist chaplain, became a committed and determined advocate for his soldiers bringing attention to their plight and eventually to the Prime Minister himself. Brown became a lone voice for a brave but powerless soldier community from within the forces of the British Empire.